Probing the local electronic structure in metal halide perovskites through cobalt substitution - Haghighirad, A; Klug, M; Duffy, L; Liu, J; Ardavan, A; van der Laan, G; Hesjedal, T; Snaith, H (Wiley, 2023)
Owing to the unique chemical and electronic properties arising from 3d‐electrons, substitution with transition metal ions is one of the key routes for engineering new functionalities into materials. While this approach has been used extensively in complex metal oxide perovskites, metal halide perovskites have largely resisted facile isovalent substitution. In this work, it is demonstrated that the substitution of Co2+ into the lattice of methylammonium lead triiodide imparts magnetic behavior to the material while maintaining photovoltaic performance at low concentrations. In addition to comprehensively characterizing its magnetic properties, the Co2+ ions themselves are utilized as probes to sense the local electronic environment of Pb in the perovskite, thereby revealing the nature of their incorporation into the material. A comprehensive understanding of the effect of transition metal incorporation is provided, thereby opening the substitution gateway for developing novel functional perovskite materials and devices for future technologies.